The affective dimension of early‐onset psychosis and its relationship with suicide. (26th September 2014) - Sanchez‐Gistau, Vanessa; Baeza, Inmaculada; Arango, Celso; González‐Pinto, Ana; de la Serna, Elena; Parellada, Mara; Graell, Montserrat; Paya, Beatriz; Llorente, Cloe; Castro‐Fornieles, Josefina
<x xml:space="preserve">Abstract</x> Background The affective dimension has scarcely been studied in early‐onset psychosis. Our aims were to investigate the prevalence and type of affective symptoms in the prodromal and acute phases of early‐onset psychosis and to examine their relationship with suicide. We also sought to establish whether the presence of premorbid antecedents or the presence of affective symptoms during the prodromal and acute phase might predict a later diagnosis of bipolar disorder (BP) or schizophrenia (SZ). Method Participants were 95 youths, aged 9–17 years, experiencing a first episode of a psychotic disorder (FEP) according to DSM‐IV criteria. Prodromal affective symptoms in the year prior to the onset of full‐blown psychosis were assessed by means of the K‐SADS. Affective symptoms during the acute episode were evaluated using the Hamilton Depression Rating Scale and the Young Mania Rating Scale. Suicidality was assessed during the acute episode and at 6 and 12 months. Results Half of the patients experienced affective symptoms during the prodrome, with depressive symptoms being the most frequently reported. During the acute episode, 23.2% presented depressive, 41.4% mixed and 18.9% manic symptoms. After logistic regression analysis, only the presence of depressive symptoms was significantly associated with suicidality during the 12 months following the FEP. Neither early premorbid antecedents nor the prevalence or type of affective symptoms during the FEP predicted a diagnosis of BP or SZ at 12 months. However, both depressive and manic prodromal symptoms were associated with a later diagnosis of BP. Conclusions The FEP of both SZ and BP is preceded by an identifiable prodromal phase. Early detection programs should target young people at clinical risk for the extended psychosis phenotype. The high prevalence of affective symptoms during the early phases of psychosis may encourage clinicians to identify and treat them in order to prevent suicide behaviour.